Poor response to direct-acting antiviral therapy in HCV-infected elderly population: a real-life cohort study based on GeneXpert® technology. (July 2018) - Wahid, Braira; Waqar, Muhammad; Saleem, Komal; Shafi, Faiza; Rehman, Zobaria; Hanif, Iqra; Ahmad, Hafiza Maleeha; Wasim, Muhammad; Sajjad,; Wahid, Khansa; Idrees, Muhammad
Aim: This study aimed to determine the efficacy of direct-acting antiviral drugs in different ethnicities and elderly population of Pakistan.Methods: We used GeneXpert ® technology to quantify HCV RNA and evaluated treatment response in different cohorts that included HCV patients classified on the basis of their age-group and ethnicity.Results: The findings of our study suggest that 76% of nonresponder patients were older than 55 years of age which shows that age is the predictor of treatment outcome of direct-acting antiviral drugs. In addition to this, no differences were observed in overall efficacy by ethnicity.Conclusion: Treatment-regimen sofosbuvir+ribavirin has a limited effect on older patients; therefore, practitioners and healthcare professionals need to reconsider treatment options for elderly populations.